142k views
3 votes
Rewrite the expression 7x^2 + 14x - 56 as three factors where one of the factors is an integer value.

Choose three factors and write an equivalent expression.

options listed:
6

7

42

(x+1)

(x-1)

(x+2)

(x-2)

(x+3)

(x-3)

(x+4)

(x-4)

User Pikapops
by
5.2k points

1 Answer

4 votes

Answer:

The factors are
7,(x-2),(x+4)


7x^(2) +14x-56=7(x-2)(x+4)

Explanation:

we have


7x^(2) +14x-56

equate the expression to zero


7x^(2) +14x-56=0

Group terms that contain the same variable, and move the constant to the opposite side of the equation


7x^(2) +14x=56

Factor the leading coefficient


7(x^(2) +2x)=56


(x^(2) +2x)=8

Complete the square. Remember to balance the equation by adding the same constants to each side


(x^(2) +2x+1)=8+1


(x^(2) +2x+1)=9

Rewrite as perfect squares


(x+1)^(2)=9

Take square root both sides


(x+1)=(+/-)3


x=-1(+/-)3


x=-1(+)3=2


x=-1(-)3=-4

therefore


7x^(2) +14x-56=7(x-2)(x+4)

User Cyboashu
by
6.1k points